2018
DOI: 10.1016/j.scitotenv.2018.01.278
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of tetracycline resistance gene transport in the Sumas River agricultural watershed of British Columbia, Canada

Abstract: Environmental transport of contaminants that can influence the development of antibiotic resistance in bacteria is an important concern in the management of ecological and human health risks. Agricultural regions are locales where practices linked to food crop and livestock production can introduce contaminants that could alter the selective pressures for the development of antibiotic resistance in microbiota. This is important in regions where the use of animal manure or municipal biosolids as waste and/or fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 52 publications
(51 reference statements)
1
12
0
Order By: Relevance
“…The differences among the three tetracycline resistance genes might be caused by different patterns of tetracycline antibiotic usage and different compositions of microflora [42]. Tetracycline resistance genes have been found to be among the most common ARGs in aquatic environments [43,44]. The levels of tetracycline resistance genes were lower than those of Tai Lake [45], but they were in agreement with those detected in the Huangpu River [41].…”
Section: Discussionmentioning
confidence: 56%
“…The differences among the three tetracycline resistance genes might be caused by different patterns of tetracycline antibiotic usage and different compositions of microflora [42]. Tetracycline resistance genes have been found to be among the most common ARGs in aquatic environments [43,44]. The levels of tetracycline resistance genes were lower than those of Tai Lake [45], but they were in agreement with those detected in the Huangpu River [41].…”
Section: Discussionmentioning
confidence: 56%
“…As reported in several previous studies, manure generated by dairy cattle may contain potentially harmful antibiotic resistant E. coli [ 36 , 37 , 38 ]. The emergence and spread of ESBL-producing E. coli associated with dairy cattle manure are of particular concern [ 39 , 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 89%
“…For some bacteria, such as Streptococcus pneumoniae and Escherichia coli, seasonality in drug resistance has been explained by the fact that there are also fluctuations in antibiotic use, which is especially high during the winter months (Sun, Klein, & Laxminarayan, ; Dagan et al, ). However, in the environment it has recently been reported that seasonal variations strongly influence specific transport patterns of tetracycline resistance genes (Keen, Knapp, Hall, & Graham, ). Therefore, the results of the present study highlight the need for further investigations in this area.…”
Section: Discussionmentioning
confidence: 99%